MICROBIAL PROFILE OF THE WOUND SURFACE IN MINE-EXPLOSIVE INJURIES - Футуйма, Юрій; Малиновська, Любов; Красій, Наталія; Романюк, Лідія (SWorldJournal, 2025)
The article discusses the relevance of microbial contamination of wounds sustained as a result of mine-blast injuries (MBI) during combat operations in the territory of Ukraine. The spectrum of microorganisms colonizing wounds at the late stages of medica